2012
DOI: 10.1371/journal.pone.0045811
|View full text |Cite
|
Sign up to set email alerts
|

Synergism and Rules from Combination of Baicalin, Jasminoidin and Desoxycholic acid in Refined Qing Kai Ling for Treat Ischemic Stroke Mice Model

Abstract: Refined Qing-Kai-Ling (QKL), a modified Chinese medicine, consists of three main ingredients (Baicalin, Jasminoidin and Desoxycholic acid), plays a synergistic effect on the treatment of the acute stage of ischemic stroke. However, the rules of the combination and synergism are still unknown. Based on the ischemic stroke mice model, all different kinds of combination of Baicalin, Jasminoidin, and Desoxycholic acid were investigated by the methods of neurological examination, microarray, and genomics analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…QKL injection has been widely used clinically to treat the acute phase of cerebrovascular disease and has displayed excellent efficacy in improving neurological function [ 10 , 11 ]. We and other investigators demonstrated that QKL injection can improve neurological function, decrease the expression of adhesion molecules, inhibit inflammatory responses, and partially restore BBB function in a rat model of brain ischemia/reperfusion injury [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…QKL injection has been widely used clinically to treat the acute phase of cerebrovascular disease and has displayed excellent efficacy in improving neurological function [ 10 , 11 ]. We and other investigators demonstrated that QKL injection can improve neurological function, decrease the expression of adhesion molecules, inhibit inflammatory responses, and partially restore BBB function in a rat model of brain ischemia/reperfusion injury [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rg1 is one of the most active and abundant steroid saponins, with antiapoptotic [ 25 ] and neuroprotective [ 26 ] effects. Stroke is more complex than initially anticipated because it is often caused by multiple molecular abnormalities, rather than being the result of a single effect [ 27 ]. Consequently, multicomponent treatments interact with multiple targets simultaneously and are considered as a rational and efficient form of therapy for complex diseases [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbs with high conditional probability are more related to the feature Zhengs. However, as TCM pays attention to the rules of composition, it is not suitable to consider each herb separately without consideration of their combination rules [ 29 – 31 ]. Apriori's algorithm [ 32 ] was used here to find out core formulas, and the minimum support was set at 0.4.…”
Section: Methodsmentioning
confidence: 99%